More than pretty pictures? How illustrations affect parent-child story reading and children's story recall - Greenhoot, Andrea Follmer; Beyer, Alisa M.; Curtis, Jennifer (Frontiers in Psychology, 2014)
Previous research showed that story illustrations fail to enhance young preschoolers’ memories when they accompany a pre-recorded story (e.g., Greenhoot & Semb, 2008). In this study we tested whether young children might benefit from illustrations in a more interactive story-reading context. For instance, illustrations might influence parent-child reading interactions, and thus children’s story comprehension and recall. Twenty-six 3.5- to 4.5-year-olds and their primary caregivers were randomly assigned to an Illustrated or Non-Illustrated story-reading condition, and parents were instructed to “read or tell the story” as they normally would read with their child. Children recalled the story after a distracter and again after one week. Analyses of the story-reading interactions showed that the illustrations prompted more interactive story reading and more parent and child behaviors known to predict improved literacy outcomes. Furthermore,in the first memory interview, children in the Illustrated condition recalled more story events than those in the Non-Illustrated condition. Story reading measures predicted recall, but did not completely account for picture effects. These results suggest that illustrations enhance young preschoolers’ story recall in an interactive story reading context, perhaps because the joint attention established in this context supports children’s processing of the illustrations.